Long-term species balance in sympatric populations: implications for Atlantic salmon and brown trout - Jose Luis Horreo; Pablo Turrero; Juliana Perez; Eva García-Vázquez (Frontiers of Biogeography)
The factors determining regional adaptation in salmonids are still unclear, but it is known that changes in their habitat imply changes in their population structure. In this preliminary study we integrate habitat data, molecular analyses (from both nuclear microsatellite and mitochondrial loci) and life-history traits (measured on archaeological vertebrae and modern scales) of two sympatric salmonid species: Atlantic salmon and brown trout. We propose that water temperature and geological characteristics changed the biogeographic patterns of these species through asymmetric migration and different (but complementary) population growth rates. As a consequence, differences in a life-history trait (mean number of years at sea) and population sizes were detected between regions, suggesting a process of substitution of Atlantic salmon by brown trout.